Experimental study on the rotating detonation engine based on a gas mixture - Xue, Sainan; Zhang, Xin; Yang, Jianlu; Liu, Denghang; Ma, Hu; Zhou, Changsheng (Frontiers in Energy Research, 2023)
A direct connection test of a rotating detonation engine was conducted. The outer and inner diameters of the annular combustors were 206 and 166 mm, respectively. High enthalpy air was used as an oxidizer, and a mixture of hydrogen, carbon monoxide, and methane was used as fuel with a volume fraction of 5/4/1. The mixture was injected through small holes, and air was injected through annular slots. The effects of combustor length, width of annular slots, and the equivalent ratio on formation, development, propagation, and flameout of rotating detonation waves were analyzed, and several modes of rotating detonation were observed. It was found that when the width of the air annular slot was within the range of 3–5 mm, the pressure of the detonation wave was augmented with an increased slot width. As width increased, detonation waves became unstable. In study test conditions, an annular slot width of 6 mm was the critical condition for the formation of stable detonation. When the slot width was 4 mm and combustor length 160 mm, the phenomena of the conversion between single and double waves, double-wave collision, and conversion of the propagation direction occurred at different equivalent ratios. When the equivalent ratio was 1.2/1 and the slot width was within the range of 3–6 mm, the slot width was inversely related to the detonation wave velocity. When the slot width was 4 mm and the equivalent ratio was 1.0/1–1.2/1, the slot width was positively correlated with the detonation wave velocity. When the combustor length was shortened to 80 mm, the propagation mode of the detonation wave was changed to a single wave first and then to a double wave in the same direction, and the velocity reduced from 1130.69 to 1024.16 m/s. The injector used in the test inhibited the propagation of back pressure from the combustor.